PCSK9 Predicts Adverse Limb Outcomes After Endovascular Revascularization in Diabetic Chronic Limb-threatening Ischemia - Biscetti, Federico; Rando, Maria Margherita; Nicolazzi, Maria Anna; Polito, Giorgia; Pecorini, Giovanni; Angelini, Flavia; Iezzi, Roberto; Eraso, Luis H.; Dimuzio, Paul J.; Pitocco, Dario; Massetti, Massimo; Gasbarrini, Antonio; Flex, Andrea (Thrombosis and Haemostasis, 2025)
Proprotein convertase subtilisin/kexin type-9 (PCSK9) plays a crucial role in pathophysiologic processes leading to limb and cardiovascular complications in diabetes, including cholesterol homeostasis, inflammation, and endothelial oxidative stress. This study examined the association between PCSK9 levels and major adverse limb events (MALEs) in patients with type 2 diabetes mellitus (T2DM) and chronic limb-threatening ischemia (CLTI) after endovascular revascularization.This prospective cohort study included 147 T2DM patients with peripheral artery disease undergoing endovascular revascularization for CLTI. Clinical assessments, including PCSK9 blood levels, were performed, and patients were followed for 12 months to monitor MALEs. Logistic regression and ROC curve analyses assessed the relationship between PCSK9 and MALEs.During follow-up, 53 patients experienced MALEs. These patients were younger and had more severe peripheral artery disease. PCSK9 levels were significantly higher in those with MALEs (410.5 ng/mL) versus those without (360.6 ng/mL). ROC analysis showed that adding PCSK9 to cardiovascular risk factors improved MALE prediction. PCSK9 levels and Rutherford 4 category were independent risk factors for MALEs.Elevated PCSK9 levels are strongly associated with increased MALE risk in T2DM patients and may influence age of presentation and disease severity in CLTI. These findings highlight PCSK9 as a potential predictive biomarker and therapeutic target for vascular complications.
Keywords: peripheral arterial disease (PAD); chronic limb-threatening ischemia (CLTI); proprotein convertase subtilisin/kexin type-9 (PCSK9)